2018
DOI: 10.3233/nre-172369
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcutaneous spinal direct current stimulation on corticospinal excitability in chronic incomplete spinal cord injury

Abstract: OBJECTIVES:This study investigated the feasibility of modulating bilateral corticospinal excitability with different polarities of transcutaneous spinal direct current stimulation (tsDCS) in chronic, incomplete spinal cord injury (SCI).METHODS:Six subjects with chronic incomplete SCI (>12 months post injury) participated in this crossover study. Intervention consisted of 3 sessions, separated by at least 1 week, in which each subject received the conditions cathodal, anodal, and sham tsDCS. Stimulation was del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…It has also been shown that spinally applied DC stimulation, apart from more local effects [17] may have effects without delay and at large distances such as regarding function of the cerebral cortex including aspects that might relate directly to pain perception [18][19][20]. These findings may be due to far field effects of the induced electric field and thus depend on the localisation of the return electrode [21][22][23]. By all reason, they could also be due to afferent activity induced in spinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that spinally applied DC stimulation, apart from more local effects [17] may have effects without delay and at large distances such as regarding function of the cerebral cortex including aspects that might relate directly to pain perception [18][19][20]. These findings may be due to far field effects of the induced electric field and thus depend on the localisation of the return electrode [21][22][23]. By all reason, they could also be due to afferent activity induced in spinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several works pinpointed the lack of standardized protocols in order to control for the tDCS-triggered neuromuscular responses [12,13]. Whatever the legitimate usage, the high viability of a compact tDCS set-up, such as a headset, might facilitate and boost muscular performance and adherence to physical activity for a variety of different populations, either recovering from depression [14], spinal cord injuries [15][16][17], or healthy subjects undergoing high-intensity training [18]. Since evidence in this field has been accumulating, particularly for favorable and safe tDCS effects on exercise capacity, it might be worthy studying an acute, user-friendly, tDCS administration prior to exercise in healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Cathodal or anodal stimulation can be applied, and corticospinal excitability evaluated in recorded muscles by TMS [135] or spinal reflexes [136]. Although nonsignificant results have been reported, modifications in MEPs suggest differences in cathodal versus anodal stimulation, meaning lateralization in responses depending on the location of the reference electrode [135]. Cathodal tsDCS stimulation did not show differences in spinal reflexes compared to sham stimulation [136].…”
Section: Electrical and Magnetic Stimulation Strategies For Evaluation Of Spinal And Supraspinal Circuits After Scimentioning
confidence: 94%
“…Few studies have used the transcutaneous spinal Direct Current Stimulation (tsDCS) technique to study motor activation in complete and incomplete SCI. Cathodal or anodal stimulation can be applied, and corticospinal excitability evaluated in recorded muscles by TMS [135] or spinal reflexes [136]. Although nonsignificant results have been reported, modifications in MEPs suggest differences in cathodal versus anodal stimulation, meaning lateralization in responses depending on the location of the reference electrode [135].…”
Section: Electrical and Magnetic Stimulation Strategies For Evaluation Of Spinal And Supraspinal Circuits After Scimentioning
confidence: 99%